Discourse of Multicultural Students in Classroom Interaction - Sa’adah, Nurul (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Discourse is an increasingly popular and important area of language study. It discusses not only about language itself but also how it relates with society, culture, and thought. It is use to described activities in several disciplines, such as linguistic, sociolinguistic and psycholinguistic. This paper aims to show the features of discourse in communication based on the culture of the students in classroom interaction.This study was conducted by using descriptive qualitative method.Discourse and culture is a part of Discourse Analysis that study about social interaction both of verbal and non-verbal interaction. The study of discourse provide insight into the way of people interact in society. Related to the culture it is more general aspect of society that goes beyond specific roles of communicators. Roughly speaking, culture can be defined as the deposit of knowledge, beliefs, values and attitudes a group of people share. As the major of discourse that focus on interaction it is related to language that use as a tool of communication. When we talking about discourse and culture we will discuss many aspects. Discourse and culture investigates many problems in discourse analysis. There are several aspects that included such as Shafir-hypothesis and many critical in discourse analysis, talking about gender, racism and intercultural communication. As a major of analysis is the way of someone to communicate each other looking up from many differences of language, such as we should consider what we will say to communicate with other people in different culture and different gender of speaker. The findings from the different culture and gender womenâs speech has been said to be more polite, redundant. formal, clearly for pronounced and complex explain about something while from menâs speech has less clearly and simple pronounced.